Evaluating the stomach content of Wild Scalloped Spiny Lobster (Panulirus homarus) - MUHAMAD AMIN; ANIS FITRIA; AKHMAD T. MUKTI; ANDI BASO MANGUNTUNGI; SHAFWAN AMRULLAH; SAHRUL ALIM; MELISSA BEATA MARTIN (Society for Indonesian Biodiversity, 2022)
Abstract. Amin M, Fitria A, Mukti AT, Manguntungi AB, Amrullah S, Alim S, Martin MB. 2022. Evaluating the stomach content of Wild Scalloped Spiny Lobster (Panulirus homarus). Biodiversitas 23: 6397-6403. The high demand for spiny lobster seeds has placed intense pressure on the lobsters’ wild stock in Indonesia. To address this issue, a hatchery was developed to produce scalloped spiny lobster larvae. However, the dietary requirements after the yolk sac has been depleted have proven to be a significant challenge. Thus, the present study aimed to identify the potential live diet of scalloped spiny lobster larvae by identifying the stomach contents of lobster larvae captured in the wild. Fifteen scalloped spiny lobsters at the post-larval stage were collected from three fishing grounds: Gerupuk Bay (Lombok Island), Tawang Bay (East Java), and Prigi Bay (East Java), Indonesia. The stomach of each scalloped spiny lobster was dissected under a dissecting microscope and its contents were observed under a binocular microscope for plankton identification and abundance. The stomach contents of scalloped spiny lobster resulted in five identified plankton species collected from Prigi Bay [Tintinnopsis sp. (37.5%), Grammatophora sp. (25%), Synedra sp. (18.8%), Phormidium sp. (4.3%), and Rhizisolenia sp. (4.3%)]; six plankton species collected from Tawang Bay [Ochromonas sp. (32.3%), Synedra sp. (20.6%), Tintinnopsis sp. (14.7%), Uronema sp. (14.7%), Coscinodiscuss sp. (2.9%), and Planktoniella sp. (2.9%)]; and six plankton species collected from Gerupuk Bay [Synedra sp. (33.3%), Chlorococcum sp. (33.0%), Phormidium sp. (13.3%), Gymnidinium sp. (6.6%), unidentified Cirripedia (3.3%), Rhizosolenia sp. (3.0%)]. Of these plankton, Synedra sp. and Rhizolenia sp. were the most common representatives in the stomach of all lobster samples. Thus, assessing these two plankton genera is highly recommended for future studies.